Composite dietary antioxidant index with hepatic indices for predicting mortality in cardiovascular-kidney-metabolic syndrome - Zheng Yang; Shupeng Song; Yongguo Li (Medicine, 2026)
Oxidative stress is a pathological driver of cardiovascular-kidney-metabolic (CKM) syndrome, exacerbating inflammation and tissue injury, while metabolic dysfunction-associated steatotic liver disease plays a central role in the progression of CKM. The Composite Dietary Antioxidant Index (CDAI), as a comprehensive measure of the overall antioxidant capacity of the diet, reflects an individual’s exposure level to dietary antioxidants. This study aimed to evaluate the predictive value of CDAI combined with hepatic indices for disease progression and mortality risk in CKM patients. Data were derived from the US National Health and Nutrition Examination Survey 2001–2018. Using methods such as multivariate Cox regression analysis, survival analysis, mediation effect analysis, and machine learning, we examined the associations of CDAI and hepatic indices – including the Fatty Liver Index, NAFLD Fibrosis Score (NFS), AST to Platelet Ratio Index, and Fibrosis-4 Index (FIB-4) – with CKM staging and the risks of all-cause and cardiovascular disease (CVD) mortality among CKM participants. The fully adjusted model revealed that participants in the highest CDAI quartile had a significantly lower risk of all-cause mortality (hazard ratio = 0.717, 95% confidence intervals: 0.611–0.841; P < .0001) and CVD mortality (23.1% reduction) compared to the lowest quartile. Restricted cubic spline (RCS) analysis confirmed a significant inverse association between CDAI and both all-cause and CVD mortality. Elevated levels of hepatic indices were associated with increased all-cause and CVD mortality risk. Kaplan–Meier curve analysis also showed an inverse association between higher CDAI and all-cause/CVD mortality, whereas hepatic fibrosis indices (FIB-4, NFS, and AST to Platelet Ratio Index) were positively associated with mortality. Mediation analysis indicated that the protective effect of CDAI was independent of the liver fibrosis pathway but partially mediated through reduced hepatic steatosis. Furthermore, Light Gradient Boosting Machine demonstrated optimal performance in predicting advanced CKM stages. Advanced age, hepatic indices (NFS, FIB-4, and Fatty Liver Index), and vitamin E levels were key predictors of advanced CKM staging. Higher CDAI is associated with reduced all-cause and CVD mortality in CKM patients, while elevated hepatic indices correlate significantly with increased mortality risk. Both CDAI and hepatic indices serve as effective predictors for CKM risk stratification.